Role of the integration of the 4C model in the professional training of foreign language teachers - Salybekova, Farida Muratovna; Almetov, Negmatzhan Shadimetovish; Karbozova, Gulnara Kumisbekovna; Suyuberdieva, Aiman Abdrazakovna; Kudaibergenova, Marzhan Ryskulbekovna; Nazarova, Gaziza Zhaldybaevna (Frontiers in Education, 2023)
This study explored the opinions and experiences of senior EFL teachers and experts regarding the appropriate training of foreign language teachers to implement the 4C (critical thinking, creativity, communication, and collaboration) model of education in foreign language teaching. To achieve this, the study employed a mixed-methods approach, using both qualitative and quantitative methods. Purposive sampling was used to select twelve participants who were the most knowledgeable and experienced in the research topic, and in-depth one-on-one interviews were conducted with them. Thematic analysis was used to identify major themes and patterns in the participants' responses. Additionally, a survey was conducted with 60 EFL students to assess the impact of the 4C training on their learning outcomes. The findings of the study revealed that participants perceived the 4C model of education as an effective approach for teaching foreign languages. They also emphasized the importance of providing appropriate training to foreign language teachers to enable them to effectively implement the 4C model. The survey data showed that the 4C training had a positive impact on the students' learning outcomes. The study contributes to the existing literature on foreign language education by providing insights into the perceptions and experiences of senior EFL teachers and experts regarding the appropriate training of foreign language teachers to implement the 4C model. The study recommends that teacher training programs be revised to include the 4C model of education to improve the quality of foreign language education in Kazakhstan.